Pátria, poesia e oceano : a poética fundacional moçambicana - Fernandes, Vanessa Pincerato (2024)
This work highlights the importance of literary research on texts published in newspapers and magazines in Mozambique, considering these publications as a collective diary that reflects the political and cultural history of the country – Mozambique. The existence of the press from 1908 onwards is vital to understanding the evolution of Mozambican literature, particularly in the 1940s and 1950s, a period marked by intense intellectual discussions about the national future. This research is dedicated to a Mozambican literary collection that spans a century, highlighting how local literature became detached from colonial influence. Literature written in African countries, especially Mozambique, during the European colonial period, went through a thematic evolution, divided into three phases, according to Mendonça (2011, p. 12): the dichotomy between “Being African and Being European”, the confrontation “Being African vs. Being European” and the tension “Being National vs. Universal Being”. This thematic progression culminates in the formation of a distinctive national literature. Mozambican poets such as José Craveirinha, Virgílio de Lemos and Rui Knopfli, through their literary production, investigate the complexities of identity in colonized spaces, exploring themes such as homeland, poetry and the ocean. From a following generation, we bring to reflect on the reunion of the waters in the ocean the presence of the poet Eduardo White, one of the founders of Revista Charrua, who presents a scenario in which the literature produced in postindependence Mozambique promotes a new configuration between the present and the past, between fiction and reality, recovering a space between what was lived and what is experienced in Mozambique. White's poetry does not escape the historicity that permeates almost all Mozambican poetry, making a notable and persistent production emerge from the dialogue between subjectivity and History. National literature, with its associated values – identity, Mozambicanness, roots, love for the country, national pride – emerges as an essential pillar in the nation-building project. Through extensive bibliographical research, we found that the journey of establishing a nation, through poetry, begins in the press, develops with poets in the colonial period and is consolidated with Revista Charrua (1984). To support this discussion, we resorted to a set of literary works that served as a basis for study: Francisco Noa (1996), Rita Chaves (2012), Fátima Mendonça (2011), Ana Mafalda Leite (1995), Carmem Tindó Secco (2006) , Jessica Falconi (2013), among others. Thus, this thesis set out to explore the complex and multifaceted interconnection between three distinct but intrinsically linked elements: Homeland, Poetry and Ocean. Divided into three chapters, each section analyzes the influence and representation of these themes in different contexts and perspectives. It is crucial to highlight the absence of a defined national project during the colonial period. The press emerges as an influential agent in the construction of a national identity, but only through the struggles for independence does this identity solidify. Thus, we will see in this work how the elements of homeland, poetry and ocean play an essential role in the formation of a foundational Mozambican poetics.